Local Wisdom-Based Marketing Strategies for Enhancing the Attractiveness of Dayak Cultural Tourism: Evidence from the 40th Pekan Gawai Dayak in 2026: English - Samuel Bong; Stanislaus Stanislaus (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Why does the author raise this topic? Essentially, this study aims to describe and analyze local wisdom-based marketing strategies in enhancing the attractiveness of Dayak cultural tourism at the 40th Pekan Gawai Dayak in 2026. This research employs a qualitative approach using a descriptive literature study method. Research data were obtained through the examination of various literature sources, including scientific journal articles, reference books, cultural documents, tourism reports, media publications, and digital promotional materials related to Dayak culture and cultural tourism development. Data analysis was conducted using content analysis techniques through the stages of source identification, data reduction, theme categorization, interpretation, and conclusion drawing. The findings indicate that local wisdom-based marketing strategies at Pekan Gawai Dayak can be developed through several main approaches, namely cultural branding, cultural storytelling, digital cultural marketing, and community-based marketing. Dayak local wisdom, reflected in customary values, cultural symbols, traditional arts, rituals, culinary heritage, and the philosophy of community life, serves as cultural capital in building tourism identity and attractiveness. Furthermore, the involvement of indigenous communities and cultural practitioners plays an important role in maintaining cultural authenticity while strengthening the image of a sustainable tourism destination. This study concludes that the integration of local wisdom into marketing strategies functions not only as a tourism promotion instrument but also as a strategy for preserving Dayak cultural identity amid the development of the modern tourism industry. This culture-based marketing model can serve as a reference for local governments, cultural event organizers, and tourism stakeholders in developing cultural tourism destinations that are authentic, competitive, and sustainable.